(untitled) (Physical Education, Health and Social Sciences, 2026)
Tehmina Durrani’s My Feudal Lord is a significant feminist memoir in Pakistani English literature because it exposes the lived realities of women under feudal patriarchy. This paper examines the depiction of women in the memoir through the theoretical lens of Gayatri Chakravorty Spivak, particularly her ideas about subalternity, silencing, and female self-representation. Using a qualitative research design and close textual reading, the paper explores how female identity is represented through domestic servitude, shame, motherhood, voicelessness, and eventual self-assertion. The study argues that women in the memoir are portrayed as socially conditioned, emotionally burdened, and structurally marginalized figures whose lives are shaped by patriarchy, marriage, class privilege, and cultural expectations. At the same time, the memoir does not reduce women to passive victims. Through Tehmina’s gradual transformation from a silenced wife into a speaking subject, the text offers a movement from endurance to resistance. The analysis demonstrates that My Feudal Lord is both a testimony of women’s oppression and a literary act of feminist recovery. It reveals how women are denied agency in patriarchal discourse, yet also how autobiographical narration enables the reclamation of female voice, dignity, and selfhood.